A Study on Economic Benefits and Transformation Paths of Precision Marketing in Sino-Kazakh Agriculture - L. Yilin; Wang Wenlan (Экономика: стратегия и практика, 2025)
Modern agricultural production needs to increase efficiency and sustainability against the background of digitalization and environmental challenges. The purpose of this study is to analyze the impact of precision marketing on the economic performance and sustainable development of agro-industrial enterprises using the example of China, as well as to assess the applicability of the Chinese experience to the agricultural sector in Kazakhstan. The methods used are econometric analysis of panel data and cross-country comparative research. Based on the panel data of ten representative listed agribusinesses in China from 2014 to 2023, the empirical study uses regression analysis and fixed effects model. The results show that the input of selling expenses is significantly positively correlated with the growth of operating revenues, with a marginal benefit as high as 1:17.04, highlighting the central role of precision marketing in resource allocation. At the same time, the strategy significantly impacts the economic efficiency and sustainable development of agribusinesses through reducing resource wastage. The coefficient of determination was R2 = 0.735, which indicates a high explanatory power of the model, and each increase in marketing costs of 100 million yuan was accompanied by an average increase in revenue of 5.165 billion yuan, which indicates a high marginal return (17 times higher than the underlying investment). Special emphasis is placed on the potential of Sino-Kazakh cooperation in the application of precision agriculture technologies such as smart irrigation and drone inspection.